Treating chronic hepatitis delta: the need for surrogate markers of treatment efficacy - Yurdaydin, Cihan; Urban, Stephan (Journal of hepatology, 2019)
Chronic hepatitis delta represents the most severe form of chronic viral hepatitis. The current treatment of hepatitis delta virus (HDV) infection consists of the use of interferons and is largely unsatisfactory. Several new compounds are currently in development for the treatment of HDV infection. However, surrogate markers that can be used to develop clinical endpoints in HDV infection are not well defined. In the current manuscript, we aimed to evaluate the existing data on treatment of HDV infection and to suggest treatment goals (possible "trial endpoints") that could be used across different clinical trials.